Gulf Economic Monitor, November 2018 : Staying the Course on Reforms - World Bank Group (Washington, DC: World Bank, 2018)
The near-tripling of oil prices from their trough in January 2016, to nearly 80 US dollars per barrel in early October 2018, has spurred a recovery in the GCC economies, following three years of persistent weakness. Additional support has come from rising oil production, and a slower pace of fiscal consolidation as government revenues have increased. Saudi Arabia emerged from recession in the first quarter of 2018 and Ku-wait, in the second quarter. The United Arab Emirates, Qatar, Oman and Bahrain posted positive economic growth rates in the first half of the year. Higher energy prices and rising oil production are also helping the GCC countries to narrow large fiscal and external deficits, which had emerged in the wake of the 2014 oil shock. On aggregate, the region is expected to post growth of 2.0 percent in 2018, following a contraction of 0.3 percent in 2017 (the first such contraction in over a decade). Looking further ahead, growth is expected to reach 2.7 percent in 2020, as high energy prices and the expiration of the OPEC agreement bolster government revenues, support higher government spending and lift domestic sentiment and activity. External and fiscal imbalances are also expected to narrow, with Saudi Arabia and the UAE achieving near fiscal balance by 2020 and, along with Qatar and Kuwait, returning to cur-rent account surpluses during 2018-20. This positive outlook is underpinned by an upward revision of our oil price forecasts from 60 US dollars a barrel for 2019-20 (in the February 2018 issue of the Gulf Economic Monitor) to 72 US dollars a barrel for that time period. Projections also assume that GCC countries will persevere with important structural reforms initiated in recent years.